ROLE OF PET-CT IN EVALUATION OF DIFFERENT TYPES OF CANCER: A RETROSPECTIVE STUDY OF CANCER PATIENTS AT A DIAGNOSTIC CENTER IN NEPAL - Shahi , Rajive Raj; Bhattarai , Babita; Khadka , Sitaram; Rijal , Thaneshwar; Lamichhane , Bisesh; Yadav , Mamata; Shah , Roshan; Yadav , Gopal Kumar; Basnet , Bina (Journal of Chitwan Medical College, 2022)
Background: Fluorodeoxyglucose (FDG) PET (Positron Emission Tomography) is used for the evaluation of different solid cancers as well as characterization of solitary pulmonary nodules. This study was conducted with objectives to determine the prevalence of various types of cancer; to assess the status of cancer in terms of progression, regression, or static; and for metastatic workup by PET-CT scan. Methods: A retrospective cross-sectional study involving 545 patients of different cancers from all over Nepal was performed at Kundalini Diagnostic Center from July 2019 to March 2020. The data were analyzed using IBM SPSS version 22. Results: The mean age of study participants was 53.91±16.63 years. Out of total 545 participants, (499, 91.56%) tested positive for cancer with PET-CT scan with a higher proportion belonging to 50-59 years age group. Half of the participants (275, 50.46%) had disease progression and one-fifth of the participants (144, 26.42%) had static disease. Majority of the patients (139, 27.85%) were diagnosed with some form of gastrointestinal tumor. Though the data was statistically insignificant, participants with age 40-60 years were 1.18 times more likely to have cancer detected (OR 1.188, 95%CI 0.46-3.02). Conclusions: PET-CT scan is a valuable tool for assessment of characteristics of different types of cancer although differentiation of primary or a second primary or metastasis may not be possible. There is no significant association between various age groups or gender with overall cancer predisposition.